2013
DOI: 10.1371/journal.pone.0067523
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface

Abstract: The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 47 publications
1
82
0
Order By: Relevance
“…If light was the primary factor promoting expression, potential sources of light during Polar darkness are bioluminescence and the Moon. Most deep-sea animals and many bacteria are bioluminescent and high levels of bioluminescence have been detected in the deep Mediterranean for periods lasting several months (Tamburini et al, 2013). This process also occurs in the Arctic, but the reported photic levels (Berge et al, 2012) are lower than those observed in the Mediterranean.…”
Section: Seasonal Trends In Pr Presence and Expressionmentioning
confidence: 99%
“…If light was the primary factor promoting expression, potential sources of light during Polar darkness are bioluminescence and the Moon. Most deep-sea animals and many bacteria are bioluminescent and high levels of bioluminescence have been detected in the deep Mediterranean for periods lasting several months (Tamburini et al, 2013). This process also occurs in the Arctic, but the reported photic levels (Berge et al, 2012) are lower than those observed in the Mediterranean.…”
Section: Seasonal Trends In Pr Presence and Expressionmentioning
confidence: 99%
“…However, since offshore convection affects large areas (see Fig. 1 in Tamburini et al, 2013), it is likely that the litter it can convey down to the deep also spreads along vast expanses of the seafloor. Dense waters involved in offshore convection eventually touch bottom at the continental rise and bathyal plain, i.e.…”
Section: Litter Interaction With Oceanographic Processesmentioning
confidence: 99%
“…The average OM photon detection efficiency drops by 5-10% in spring and partly recovers in the second half of the year. This might be related to the formation of dense deep-sea water through a process known as "opensea convection" [22]. As a consequence of such an exchange of deep sea water, sedimentation as well as biofouling processes might impact the OM photon detection efficiencies in these periods.…”
Section: Resultsmentioning
confidence: 99%